Coordination Decision of Multi Ｒegions Available Transmission Capacity Based on Improved NSGA-Ⅱ - JIANG Jian; ZUO Hong-ji; XIONG Hua-hua; LI Shu-qiang; FU Guo (Journal of Harbin University of Science and Technology)
In electricity market environment，reasonable calculation of available transmission capacity can protect the economic interests of both parties. In order to solve the multi-objective optimization problem，the non-dominated sorting genetic algorithm ( NSGA-II) is premature and has poor convergence performance. In this paper， it is improved to build a variety of groups to enhance the competitive advantage between the populations，and the multi-crossing operators are used to iterate alternately to enhance the local search ability of the individuals in the optimal solution concentration，so that they can converge to the optimal solution quickly. In order to keep more dominant individuals in various groups，the sub-population size is adjusted automatically. Taking the ATC coordination optimization from a certain region in China to the region in and out of the province as an example，the result of the improved NSGA-II algorithm is superior to that of NSGA-II algorithm in convergence performance and more reasonable solution results.